2006
DOI: 10.1002/neu.20325
|View full text |Cite
|
Sign up to set email alerts
|

Consistent dynamics suggests tight regulation of biophysical parameters in a small network of bursting neurons

Abstract: The neuronal firing patterns in the pyloric network of crustaceans are remarkably consistent among animals. Although this characteristic of the pyloric network is well-known, the biophysical mechanisms underlying the regulation of the systems output are receiving renewed attention. Computer simulations of the pyloric network recently demonstrated that consistent motor output can be achieved from neurons with disparate biophysical parameters among animals. Here we address this hypothesis by pharmacologically ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…In the control condition, the oscillations of the PY and LP neurons are driven by the AB/PD pacemaker core. Previous studies in the spiny lobster, Panulirus interruptus, show that blocking I A with 4-AP increases the burst frequency and intraburst spike frequency of the pyloric neurons, suggesting an increased excitability (Tierney and Harris-Warrick 1992;Szücs and Selverston 2006). Our results also showed increased PD burst cycle frequency at 400 µM and higher 4-AP concentrations.…”
Section: The Role Of I a In Modulating The Phase In The Pyloric Networksupporting
confidence: 82%
See 1 more Smart Citation
“…In the control condition, the oscillations of the PY and LP neurons are driven by the AB/PD pacemaker core. Previous studies in the spiny lobster, Panulirus interruptus, show that blocking I A with 4-AP increases the burst frequency and intraburst spike frequency of the pyloric neurons, suggesting an increased excitability (Tierney and Harris-Warrick 1992;Szücs and Selverston 2006). Our results also showed increased PD burst cycle frequency at 400 µM and higher 4-AP concentrations.…”
Section: The Role Of I a In Modulating The Phase In The Pyloric Networksupporting
confidence: 82%
“…Studies show I A channel mRNA shal is expressed in both the pyloric and gastric mill neurons (Baro et al 1997;Schulz et al 2007). I A decreases the burst period and alters the relative phase between pyloric neurons in the spiny lobster, Panulirus interruptus (Tierney and Harris-Warrick 1992;Szücs and Selverston 2006). However, little is known about the function of I A in modulating the dynamics of the gastric mill neurons in the American lobsters.…”
Section: Introductionmentioning
confidence: 96%
“…It has been shown that the pyloric rhythm is very consistent from animal to animal [4], [7] during development of body size [8], under natural [9] and artificial perturbations [10], and even after decentralization [11][13]. Furthermore, the cells generating this rhythm exhibit stereotyped dynamics and can be identified by visual inspection of intracellular recordings and comparison to simultaneous extra-cellular recordings of identified nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Both modeling and experimental studies demonstrate that similar circuit function can result from a large variation in the synaptic and intrinsic conductances that contribute to circuit function (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). This finding suggests that each individual could, during development, build a brain that differs significantly from all others and poses the question of whether circuits with diverse underlying structure, yet similar behavior, can respond reliably (12,13) to neuromodulatory substances that alter brain states (14)(15)(16)(17)(18)(19)(20)(21). Therefore, we used the dynamic clamp (22,23) to construct 2-cell circuits (24) from neurons of the crab stomatogastric ganglion (STG).…”
mentioning
confidence: 99%